1996
DOI: 10.1055/s-2006-957972
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Stilbene Glucoside, Oxyresveratrol 3′ -O-β-Glucopyranoside, from the Root Bark ofMorus alba

Abstract: A novel stilbene glucoside was isolated from the root bark of Morus alba L. (Moraceae), along with mulberroside A, cis-mulberroside A, oxyresveratrol. The structure of the novel stilbene glucoside was determined as oxyresveratrol 3'-O-beta-glucopyranoside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…The reference standards of RES and carbamazepine, the internal standard (IS), were purchased from National Institute for the Control of Pharmaceutical and Biological Products (Beijing, China). OXY was isolated from the roots of S. china, and its spectral data were consistent with the literature (Qiu et al, 1996;Hirakura et al, 1985). The purity of OXY was 98% using HPLC.…”
Section: Methodssupporting
confidence: 73%
“…The reference standards of RES and carbamazepine, the internal standard (IS), were purchased from National Institute for the Control of Pharmaceutical and Biological Products (Beijing, China). OXY was isolated from the roots of S. china, and its spectral data were consistent with the literature (Qiu et al, 1996;Hirakura et al, 1985). The purity of OXY was 98% using HPLC.…”
Section: Methodssupporting
confidence: 73%
“…1) was extracted from the roots of Smilax china by the author. Its structure was identifi ed by comparison of its spectral data with those reported in literature (Qiu et al, 1996), and its purity was over 98% by HPLC analysis. Acetonitrile was of HPLC grade (Honeywell International Inc., USA and Tedia Co. Inc., USA).…”
Section: Experimental Materialsmentioning
confidence: 96%
“…Although many compounds such as stilbenes, flavonoids, benzofuran derivatives, and coumarins have been identified in Morus alba [2 -6], there have been few reports on its pharmacological properties. In our previous study, we investigated the absorbed constituents in rats following oral administration of the H 2 O extract of the bark of Morus alba [7] [8], and several stilbene derivatives were identified in the plasma, urine, and bile of rats. Further pharmacological studies showed that mulberroside A, a major stilbene constituent in the H 2 O extract, displayed a significant antitussive and antiasthmatic effect in animals [9].…”
mentioning
confidence: 99%
“…This article reports the isolation and structural elucidation of the three new stilbene glycosides 1 -3 1 ), the novel arylbenzofuran derivative 4, and the new coumarin glycoside 5. Ten known compounds were identified as mulberroside A (6) [10], cismulberroside A [2] [12], scopoletin (¼ 7-hydroxy-6-methoxy-2H-benzopyran-2-one) [13], and 6-hydroxycoumarin 7-O-b-d-glucopyranoside (¼ 6,7-dihydroxycoumarin 7-(b-d-glucopyranoside)) [14] by comparison with the reported data. Three compounds, i.e., 7 -9, were found for the first time in Morus alba.…”
mentioning
confidence: 99%